2014
DOI: 10.1016/j.stem.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Control of Induced Pluripotency

Abstract: Deciphering the mechanisms of epigenetic reprogramming provides fundamental insights into cell fate decisions, which in turn reveal strategies to make the reprogramming process increasingly efficient. Here we review recent advances in epigenetic reprogramming to pluripotency with a focus on the principal molecular regulators. We examine the molecular trajectories connecting somatic and pluripotent cells, genetic and chemical methodologies for inducing pluripotency, the role of endogenous master transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 129 publications
3
98
0
1
Order By: Relevance
“…This could be due to the time it took Brg1 and Baf155 to reach critical expression levels after retroviral transduction, causing them to act inefficiently during the critical window of intermediate reprogramming when transduced at later stages. These findings are consistent with previous conclusions showing that chromatin remodeling components act at an intermediate stage of reprogramming [2,13]. Interestingly, we found that Baf155 overexpression does not affect the pluripotency of hiPSCs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This could be due to the time it took Brg1 and Baf155 to reach critical expression levels after retroviral transduction, causing them to act inefficiently during the critical window of intermediate reprogramming when transduced at later stages. These findings are consistent with previous conclusions showing that chromatin remodeling components act at an intermediate stage of reprogramming [2,13]. Interestingly, we found that Baf155 overexpression does not affect the pluripotency of hiPSCs.…”
Section: Discussionsupporting
confidence: 94%
“…Replacement by ME specifiers proposed the "seasaw model" of reprogramming mechanisms. In addition, depending on reprogramming factors using a "stochastic model, a deterministic model or a combination of both as well as a biphasic model" have been proposed to understand reprogramming mechanisms [13]. It has been shown that Oct4 deficient oocytes are capable of reprogramming somatic nuclei by somatic cell nuclear transfer (SCNT) with efficiency similar to normal oocytes [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 In studying aspects of somatic cell reprogramming related to pluripotency, dramatic and complex molecular changes at the genetic, epigenetic, and metabolic levels have been observed during the initial stage of reprogramming. 2 Cell reprogramming faces the challenge of balancing stability and plasticity and must overcome critical barriers, such as cell cycle checkpoints, the mesenchymal-epithelial transition, and metabolic reprogramming, to progress cell fate conversion from a stochastic early phase toward pluripotency. 3 The p53 pathway limits cell fate transition by inducing classical signaling that leads to cell cycle arrest, senescence, or apoptosis to maintain genome stability in the face of reprogramming-induced stress.…”
mentioning
confidence: 99%
“…In addition, interference with DNMT1 promotes iPSC formation, also supporting that DNA methylation is a feature limiting reprogramming to pluripotency [101] . All reprogramming techniques involve demethylation of the genome thus appearing as a crucial process for successfully achieving pluripotency [120,121] .…”
Section: Reprogramming Factors and Epigenetic Mechanismsmentioning
confidence: 99%